Multiplexed storage and real-time manipulation based on a multiple degree-of-freedom quantum memory - Tian-Shu Yang; Zong-Quan Zhou; Yi-Lin Hua; Xiao Liu; Zong-Feng Li; Pei-Yun Li; Yu Ma; Chao Liu; Peng-Jun Liang; Xue Li; Yi-Xin Xiao; Jun Hu; et al. (Nature Communications, 2018)
Multiplexing of quantum memories would enable higher communication rate for repeater based quantum networks. Here, the authors demonstrate multiplexed storage of single-photon-level pulses using multiple degree-of-freedom, with the additional function of arbitrary manipulation of photonic pulses in real time.